Immobilization of Saccharomyces cerevisiae Cystathionine γ-Lyase and Application of the Product to Cystathionine Synthesis - Yamagata, Shuzo (American Society for Microbiology, 2004)
Cystathionine γ-lyase of Saccharomyces cerevisiae was immobilized to aminohexyl-Sepharose through the cofactor pyridoxal 5′-phosphate and was characterized with respect to its cystathionine γ-synthase activity. The immobilized product was so stable that it repeatedly catalyzed as many as five cycles of the reaction without losing activity.